Senses by Seasons: Tourists’ Perceptions Depending on Seasonality in Popular Nature Destinations in Iceland - Anna Dóra Sæþórsdóttir; C. Michael Hall; Þorkell Stefánsson (Sustainability, 2019)
Seasonality in visitor arrivals is one of the greatest challenges faced by tourist destinations. Seasonality is a major issue for sustainable tourism as it affects the optimal use of investment and infrastructure, puts pressure on resources and can create negative experience of crowding at destinations. Peripheral areas commonly experience more pronounced fluctuations in visitor arrivals. Iceland is one of those destinations. Although the number of tourists visiting the country has multiplied in recent years, seasonality is still a major challenge, especially in the more rural peripheral areas of the country. Iceland’s high season for tourism occurs during its brief summer (June to August), but in recent years more people visit the country on shorter winter trips, creating new management challenges. This research is based on an on-site questionnaire survey conducted in seven popular nature destinations in Iceland which compares the experience of summer and winter visitors. The results show that winter visitors are more satisfied with the natural environment while their satisfaction with facilities and service is in many cases lower. The areas are generally perceived as being more beautiful and quieter in winter than in summer. However, most destinations are considered less accessible and less safe in the winter. Tourists are much less likely to experience physical crowding during winter, although winter visitors are more sensitive to crowds, most likely because of expectations of fewer tourists. Finally, this research shows that tourists are less likely to encounter negative effects of tourism on the environment in the winter, (e.g., erosion or damage to rocks and vegetation), than in summer. The results highlight the importance of understanding visitor perceptions in a seasonal and temporal context.